This document confirms it. Non-narrative documents in science fiction literature - Martínez Cantón, Clara Isabel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article focuses on a type of recognizable sections or fragments of text that are frequently introduced in the science fiction novel: the non-narrative fictional documents. These types of documents appear as excursuses of the narration and are characterized because they do not advance the narrative thread. We study the functions that these documents fulfil within the narrative and why they are more characteristic and relevant in the genre of science fiction.